Resource planning with computer simulation in a semiconductor backend manufacturing environment - Liew, Kee Min. (2008)
This dissertation proposed the utilisation of computer simulation as an objective and optimal approach for the comparative efficiency evaluation of critical resources such as equipment, operators and service technicians.